METAFISIKA SUBSTANSI ILMU LOGIKA - Hidayat, Ainurrahman (STAIN PAMEKASAN, 2016)
remains necessary to guide to think and to have valid conclusion in daily life. Good and wise deed could be created from a process of thinking and concluding that are simply right and true. To comprehend Logic as a science from the perspective of substantial metaphysics, it is essential to recognize the focus of the problems as framework. The focus of the problems are 1) is Logic a substance? 2) Which one is the aspect of relation-autonomy in Logic? 3)Â Which one is the aspect of renewable-permanence in Logic? 4) Which one is the aspect of transedence-imanence in Logic? 5) What is the essence of Logic in term of normative-ontological-transcendent? This is a library research that collected the whole data from library data. The researcher, as the main instrument, highly determines the data that must be firstly gathered. The early data give direction about aspects that must be studied from the library resources hence it is able to clarify the research map in accordance with formal object and research materials. The result indicates that firstly, Logic that is on the basis of metaphysic-substance perspective is a substance containing the aspects of autonomy relation, permanence-renewable, and immanence-transcendence. Secondly, the aspect of logic autonomy, it is a direct and indirect conclusion drawing as truth form. The relation aspect of logic is the epistemology as material truth. Thirdly, the aspect of permanence of logic, it is the basic principles of thought that are divided into four fundamental principles. The renewable aspect of logic has been the history of logic development. Fourthly, the immanence aspect of logic is proposition. The transience aspect of logic is term of comprehension and existence. Fifthly, the development of logic that relies on the analysis of logic essence on the way of normative-ontology-transcendental must produce a syllabus of Logic that focus on containing the aspects of autonomy relation, permanence-renewable, and immanence-transcendence. Those aspects are the consequences of Logic from the perspective of substance metaphysics.